AKIBAT HUKUM ATAS WANPRESTASI DALAM PERJANJIAN UTANG PIUTANG (STUDI KASUS PUTUSAN PENGADILAN NEGERI INDRAMAYU NOMOR 1/PDT.G/2021/PN IDM) - Berhimpon, Eliezar; Ardiansyah (Neolectura, 2024)
In the business world, contractual relationships often involve agreements between two parties, each of whom has obligations or